Autologous Blood Transfusion in Surgical Outreach Camp - Sharma, Apurb; Bhattarai, Balkrishna (Journal of Society of Anesthesiologists of Nepal, 2015)
Poor access to healthcare including surgical care is one of the known problems faced by people living in the remote terrains of Nepal. Reaching to the community with the help of health camps has been exercised for many years in Nepal. However, surgery in such camps is often hindered by many obstacles including unavailability of blood products, lack of or poor storage facility for donated blood. Surgery often needs to be deferred in otherwise healthy patients with rare blood groups. Autologous blood collection with acute normovolaemic haemodilution is one of the blood sparing techniques used in cases where it is difficult to get matched blood or when allogenic blood cannot be used. We report a case of autologous blood collection and subsequent transfusion in a patient undergoing vaginal hysterectomy and pelvic floor repair performed at a surgical outreach camp organized in a remote district of Nepal. Journal of Society of Anesthesiologists of Nepal 2015; 2(1): 28-30